2021
DOI: 10.1007/s12311-021-01282-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Changes in Spinocerebellar Ataxia Type 3: A Systematic Review with a Narrative Design

Abstract: Spinocerebellar ataxia type 3 (SCA3), the commonest dominantly inherited ataxia worldwide, is characterized by disruption in the cerebellar-cerebral and striatal-cortical networks. Findings on SCA3-associated cognitive impairments are mixed. The classification models, tests and scoring systems used, language, culture, ataxia severity, and depressive symptoms are all potential confounders in neuropsychological assessments and may have contributed to the heterogeneity of the neurocognitive profile of SCA3. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 91 publications
2
11
0
Order By: Relevance
“…This finding is consistent with the cerebellum's role in EF processing due to its extensive reciprocal connections with areas of the cerebrum, including the prefrontal and posterior parietal cortex and the basal ganglia (Stoodley and Schmahmann, 2010;Bostan et al, 2013). Contradictorily, no correlation was found with the prefrontal-striatal circuit, which is impaired in SCA3 and plays a crucial role in higherorder cognitive functions (Alexander et al, 1986;Yap et al, 2022b). Instead, strong correlations were found between general intelligence and precentral gyrus and superior occipital gyrus (De Rezende et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This finding is consistent with the cerebellum's role in EF processing due to its extensive reciprocal connections with areas of the cerebrum, including the prefrontal and posterior parietal cortex and the basal ganglia (Stoodley and Schmahmann, 2010;Bostan et al, 2013). Contradictorily, no correlation was found with the prefrontal-striatal circuit, which is impaired in SCA3 and plays a crucial role in higherorder cognitive functions (Alexander et al, 1986;Yap et al, 2022b). Instead, strong correlations were found between general intelligence and precentral gyrus and superior occipital gyrus (De Rezende et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…The presence of clinical syndrome may compound each other; that is, ataxia and dystonia may exacerbate each other when measured with their respective clinical scales. Likewise, motor impairment is often a confounding factor for clinical scales from truly reflecting cognitive impairment (Yap et al, 2022b). This issue is often exacerbated as few tests assess only a single domain (i.e., true process-pure tests), thereby affecting the test utility in the cerebellar patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding fits with the cognitive (and affective) functions of the cerebellum, through connections with cortical and limbic structures ( Schmahmann & Sherman, 1998 ). A recent systematic review concluded that the neurocognitive profile of SCA3 is mainly characterized by impairments of executive function ( Yap et al, 2021 ). Prefrontal-striatal circuitry is implied in such higher-order cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological studies in SCA3 have revealed variable neuronal loss in cerebellum, brainstem, thalamus, subthalamic nucleus, pallidum, and motor cortex ( RĂźb et al, 2008 , RĂźb et al, 2013 , Seidel et al, 2012 ). The cerebellum is most severely affected, with ataxia as the presenting and most prominent feature, but patients may also develop pyramidal and extra-pyramidal signs, neuropathy, oculomotor dysfunction, and cognitive problems ( Pilotto and Saxena, 2018 , Ruano et al, 2014 , Yap et al, 2021 ). More than direct effects of local pathology, clinical manifestations are likely to be a consequence of more widespread functional changes in cerebellar-thalamo-cerebral and striatal-cortical networks.…”
Section: Introductionmentioning
confidence: 99%